Resilient bacteria making our antibiotics ineffective - Editorial Staff, Editorial Staff (Operating Room Nurses Association of Canada Journal, 1987)
Even after a successful operation, the risk of postsurgical complications is still very real, particularly those complications that are caused by infection.